Bimetallic Ni–Cu/ZSM-5 Catalysts for Enhanced Phenol and Vanillin Production from Benzyl Phenyl Ether and Lignin - Arnia Putri Pratama; Iman Abdullah; Yuni Krisyuningsih Krisnandi (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Bio-based phenolic chemicals from lignin represent a sustainable alternative to fossil aromatics. This study examines the catalytic conversion of benzyl phenyl ether (BPE) and compares its reactivity with isolated lignin from raw woody biomass waste (ILWB). Hierarchical ZSM-5 zeolite catalysts were synthesized and modified with bimetallic Ni–Cu and monometallic (Ni⁰ and Cu⁰) species. Catalyst characterization by Fourier Transform Infra-Red (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscope - Energy Dispersive X-Ray (SEM-EDX), X-ray Fluorescence (XRF), and Brunauer, Emmett, and Teller (BET) surface area confirmed distinct physicochemical features for each catalyst. Catalytic reactions were conducted in a batch reactor at 100–300 °C for 30 minutes. Products were analyzed by HPLC, identifying phenol and vanillin as key products. The bimetallic Ni–Cu/ZSM-5 catalyst exhibited alloy formation, producing a synergistic effect that enhanced catalytic activity. BPE conversion reached 94.29%, with a phenol yield of 32.25% at 250 °C. Additionally, ILWB lignin was readily converted, achieving 75.31% conversion and a vanillin yield of 15.85% at 200 °C. These findings confirm that Ni–Cu-modified hierarchical ZSM-5 demonstrates superior catalytic behavior for the valorization of lignin and its model compound into high-value chemical products. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).